Evaluation of School-Based Stress Management Programs on Adolescent Well-Being in Selected Higher Secondary School, Coimbatore. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Adolescence is a transitional stage marked by emotional volatility, identity formation, and increasing social and academic demands. The World Health Organization (WHO, 2021) estimates that one in seven adolescents worldwide experiences a mental health condition, with stress being one of the leading contributors to anxiety, depression, and behavioural issues. (1) Schools are an ideal setting for implementing preventive mental health interventions as they provide structured environments and reach large populations during formative years (Kieling et al., 2019). School-based stress management programs—comprising relaxation techniques, mindfulness, and life skills training—aim to enhance coping capacity, emotional regulation, and resilience (2). Tamil Nadu state has recently expanded several mental-health initiatives and school-focused programs. Media and government reports highlight initiatives such as school-level digital-safety and well-being modules (e.g., “Agal Vilakku” for girl students) and district/PHC-level mental-health services expansion (suicide prevention and targeted programmes such as “Magizhchi” in some districts including Coimbatore). These policy moves create an enabling environment for scaling school mental-health programs but also emphasize the need to evaluate implementation and equity across districts. This study evaluates the effectiveness of a structured stress management program conducted among adolescents to determine its impact on stress reduction and improved well-being.